2007
DOI: 10.18785/gcr.1902.06
|View full text |Cite
|
Sign up to set email alerts
|

Relative Abundance of Pelagic Sharks in the Western North Atlantic Ocean, Including the Gulf of Mexico and Caribbean Sea

Abstract: Little information exists on the status of pelagic shark populations in the Atlantic Ocean, especially in the Gulf of Mexico and Caribbean Sea. We derived indices of relative abundance for pelagic sharks based on mandatory logbooks and observer reports from a scientific observer program of the United States (US) pelagic longline fleet. Time series data from the pelagic longline logbook program (1986)(1987)(1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 5 publications
1
31
0
1
Order By: Relevance
“…This is attributable to several features of these tracks: (1) individuals remained within 500 km of the tagging site during May and part of June (2) limited displacement (<500 km from Cat Island) of 22.2% of tagged individuals in subsequent months and (3) the return of the individuals that left the EEZ after 60–160 days (philopatry). Pelagic longlining was prohibited by The Bahamas in the 1990 s, which may have helped conserve oceanic whitetips in this area even as they declined elsewhere in the North Atlantic [4]. The Bahamas subsequently reinforced this measure with a commercial trade ban on all sharks in 2011.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is attributable to several features of these tracks: (1) individuals remained within 500 km of the tagging site during May and part of June (2) limited displacement (<500 km from Cat Island) of 22.2% of tagged individuals in subsequent months and (3) the return of the individuals that left the EEZ after 60–160 days (philopatry). Pelagic longlining was prohibited by The Bahamas in the 1990 s, which may have helped conserve oceanic whitetips in this area even as they declined elsewhere in the North Atlantic [4]. The Bahamas subsequently reinforced this measure with a commercial trade ban on all sharks in 2011.…”
Section: Discussionmentioning
confidence: 99%
“…Oceanic whitetips were historically abundant, replacing primarily temperate-dwelling blue sharks ( Prionace glauca ) as the numerically dominant pelagic shark at lower latitudes [2]. Several studies have shown substantial population declines in oceanic whitetips, most likely related to mortality associated with the global shark fin trade [4][6]. This species is now listed as “Critically Endangered” in the Northwest Atlantic and “Vulnerable” globally by the International Union for the Conservation of Nature (IUCN) [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, the reduction in U.S. commercial PLL fishing effort in recent years has presumably reduced the relative scale of impacts by this fishery. Excluding 1991 for which data was absent, the average annual catch weight of blue sharks from 1990 to 1999 was more than 50-fold higher in recreational (hook) than in U.S. commercial PLL fisheries (annual range of 9-340 mt [annual mean value of 114 mt] for recreational; 0.12-8.00 mt [annual mean value of 2 mt] for commercial) (Cortés 2002). So in fact, targeted or incidental capture of sharks in U.S. recreational (hook) fisheries may have posed a more significant threat to certain shark populations even before fishing effort by the U.S. domestic PLL fleet decreased to it current levels, and presumably continues to eclipse commercial catch rates of certain pelagic shark species.…”
Section: Synthesis and Next Stepsmentioning
confidence: 99%
“…Indeed, many shark populations have declined with respect to their pre-exploited biomass (Baum & Myers 2004;Shepherd & Myers 2005;Cortés et al 2007), raising concern for their conservation and requiring the development of management planning.…”
Section: Introductionmentioning
confidence: 99%